The influence of silicon-doped hydroxyapatite nanoparticles on the properties of novel bionanocomposites based on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) - Mualla Öner; Semra Kirboga; Emrah Sefik Abamor; Kubra Karadas; Zeynep Kral (eXPRESS Polymer Letters, 2023)
In this study, silicon-doped hydroxyapatite (SiHAP) nanoparticles and poly(hydroxybutyrate-co-3-hydroxyvalerate, PHBV) were used to develop biodegradable ‘green’ composites due to their intrinsic biodegradability and biocompatibility properties. The novel bionanocomposites were prepared by melt compounding with 0.5, 2, and 3 wt% of SiHAP content. The fracture surface of the bionanocomposites samples from scanning electron microscopy (SEM) exhibited good dispersion of SiHAP in the PHBV matrix at 0.5 wt%. X-ray diffraction (XRD) measurements showed an enhancement of the crystallinity of the PHBV matrix, thereby acting as a nucleating agent, increasing polymer crystallinity from 50 to up to 73% at 3 wt% loadings. Dynamic mechanical analysis (DMA) was used to measure the composite and neat samples’ storage modulus, loss modulus, and damping factor under an oscillating load. DMA analysis showed an increase in storage modulus of 80% at 20 °C and 0.5 wt% SiHAP loadings. Thermal gravimetric analysis (TGA) results showed that the thermal stability of PHBV is slightly decreased by adding 2 and 3 wt% SiHAP. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) Assay and 4′,6-diamidine-2′-phenylindole dihydrochloride (DAPI) staining experiments have demonstrated that PHBV/SiHAP composites exhibit good in vitro bioactivity due to the silicon-doped hydroxyapatite nanoparticles. It is concluded that the addition of SiHAP can be a viable strategy for obtaining novel bioactive and biodegradable nanocomposites with improved mechanical and biological properties for potential medical application.